Analyzing Query Execution for Integrity Constraint Violation Detection - dos Santos, Alessandro Neves; Pena, Eduardo H. M. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2024)
Data consistency ensures the validity and integrity of data representing real-world entities. Denial constraints (DCs) generalize various integrity constraints, providing a powerful way to define rules that ensure data consistency. This work analyzes the capabilities of relational database management systems (RDBMSs) to detect DC violations in different metrics. We explore various SQL patterns for measuring DC violations and evaluate the performance of multiple RDBMSs with extensive experiments, highlighting potential performance improvements, choke points, and limitations when using them.